Pelatihan Pengembangan Minat dan Bakat Siswa di SMAN 1 Tanjung Jabung Barat Provinsi Jambi - Mohamad Muspawi; K.A. Rahman; Amirul Mukminin; Robi Hendra (Jurnal Pengabdian UNDIKMA, 2021)
The implementation of this service activity aims to improve the understanding and ability of teachers at SMAN 1 Tanjung Jabung Barat in implementing strategies for developing student interests and talents. Using lecture methods, simulations, individual and group presentations with the duration of activities for one month according to the schedule. This activity involved 6 teachers and 20 students as participants. The result of this community service activity is that the participants have the understanding and ability to implement strategies for developing student interests and talents. it is suggested to the school, especially to the principal and teachers to be able to follow up this activity on a wider scale, so that the interests and talents of the students can be detected properly and can also be developed to the fullest.